Certified Ethical Hacker (CEH) Foundation Guide - Rahalkar, Sagar Ajay (Books for professionals by professionals, 2016)
Prepare for the CEH training course and exam by gaining a solid foundation of knowledge of key fundamentals such as operating systems, databases, networking, programming, cloud, and virtualization. Based on this foundation, the book moves ahead with simple concepts from the hacking world. The Certified Ethical Hacker (CEH) Foundation Guide also takes you through various career paths available upon completion of the CEH course and also prepares you to face job interviews when applying as an ethical hacker. The book explains the concepts with the help of practical real-world scenarios and examples. You'll also work with hands-on exercises at the end of each chapter to get a feel of the subject. Thus this book would be a valuable resource to any individual planning to prepare for the CEH certification course. In this book you will: Gain the basics of hacking (apps, wireless devices, and mobile platforms) Discover useful aspects of databases and operating systems from a hacking perspective Develop sharper programming and networking skills for the exam Explore the penetration testing life cycle Bypass security appliances like IDS, IPS, and honeypots Grasp the key concepts of cryptography Discover the career paths available after certification Revise key interview questions for a certified ethical hacker